A hospital-based study of bloodstream infections in febrile patients in Dhulikhel Hospital Kathmandu University Teaching Hospital, Nepal - Nastu P. Sharma (2018)
The etiology of bloodstream infections in febrile patients remain poorly characterized in Nepal. A retrospective study of febrile patients presenting to Dhulikhel Hospital Kathmandu University Teaching Hospital from July 2002 to June 2004 was performed to evaluate the etiology of bloodstream infections and the drug sensitivity patterns of cultured organisms. The medical and laboratory records of all febrile patients with an axillary temperature ≥38°C who had a blood culture taken (n=1,774) were retrieved and analyzed. Of these, 122 (6.9%) patients had positive blood cultures, of which 40.1% were age 11 to 20 years. The male to female ratio was 1.7:1. Antibiotics had been taken prior to hospital presentation by 39 (32%) patients. Salmonella enterica serovar Typhi and serovar Paratyphi A were isolated in 50 (41.0%) and 13 (10.7%) cases, respectively. All S. Typhi and S. Paratyphi isolates were susceptible to ceftriaxone, while susceptibility to ciprofloxacin and chloramphenicol was recorded in 94.8% and 94.5% of cases, respectively. Cephalexin and amoxicillin had the lowest rates of susceptibility (64.2% and 54.1%, respectively). Salmonella spp were usually sensitive to chloramphenicol. These findings provide clinicians in this region of Nepal with a better understanding of the spectrum of pathogens causing bloodstream infections and will help guide empiric antibiotic choice.